UNE PERSPECTIVE SÉMANTIQUE INTÉGRALISTE SUR L’INTERFÉRENCE TEXTE-MUSIQUE DANS LE CAS DU THÉÂTRE MUSICAL - Mirona BENCE-MUK (Studia Universitatis Babeş-Bolyai. Musica)
The present article focuses its investigation on the place of direct and private interference of the literary text with mu100sic, being consequently dedicated to the “semantic-integralist” analysis reguarding a complete cultural-artistic object which is the musical theatre. Our approach follows the same evolution of the metaphorical dynamics, identified initially in the libretto Così fan tutte, outlining a parallel with the metaphoric dynamics of the musical discourse, by using the same strategies: dia-endo-epi-phorics. Thus, our aim is to approach the integralist theses oriented, up to the present time, only towards the literary text, to another universe of cultural and artistic creation: the musical theatre. These correspondences refer to the existence of particular metaphoric strategies within the musical discourse, collaborating from the same position with the above mentioned strategies, presented in the text of the libretto in order to enhance the mystery and to articulate the metaphorical meaning existent in the final artistic text: libretto accompanied by the musical discourse.